Isotopic Ratios of Tropical Methane Emissions by Atmospheric Measurement. Issue 9 (25th September 2017) - Brownlow, R.; Lowry, D.; Fisher, R. E.; France, J. L.; Lanoisellé, M.; White, B.; Wooster, M. J.; Zhang, T.; Nisbet, E. G.
Abstract: Tropical methane sources are an important part of the global methane budget and include natural wetlands, rice agriculture, biomass burning, ruminants, fossil fuels, and waste. δ 13 CCH4 can provide strong constraints on methane source apportionment. For example, tropical wetlands in this study give δ 13 CCH4 values between −61.5 ± 2.9‰ and −53.0 ± 0.4‰ and in general are more enriched in 13 C than temperate and boreal wetlands. However, thus far, relatively few measurements of δ 13 CCH4 in methane‐enriched air have been made in the tropics. In this study samples have been collected from tropical wetland, rice, ruminant, and biomass burning emissions to the atmosphere. Regional isotopic signatures vary greatly as different processes and source material affect methane signatures. Measurements were made to determine bulk source inputs to the atmosphere, rather than to study individual processes. These measurements provide inputs for regional methane budget models, to constrain emissions with better source apportionment. Key Points: Methane δ 13 C isotopic signatures have been measured in the tropics for wetland, rice, ruminant, and biomass burning Wetlands, rice, and ruminants are depleted in 13 C, but it is difficult to distinguish between them; biomass burning values are enriched in 13 C Isotopic measurements are essential in determining the causes of methane growth Plain Language Summary: Tropical methane sources are an important part of the global methane budget and include natural wetlands, rice agriculture, biomass burning, ruminants, fossil fuels, and waste. Carbon isotopes in methane can provide strong constraints on methane source apportionment. However, thus far, relatively few measurements of carbon isotopes in methane‐enriched air have been made in the tropics. In this study samples have been collected from tropical wetland, rice, ruminant, and biomass burning emissions to atmosphere. Regional isotopic signatures vary greatly as different processes and source material affect methane signatures. Measurements were made to determine bulk source inputs to the atmosphere, rather than to study individual processes, to provide inputs for regional methane budget models, and to constrain emissions with better source apportionment.